2013
DOI: 10.1097/iae.0b013e3182618d2e
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Medium-Chain Triglycerides Used as an Intraocular Tamponading Agent in an Experimental Vitrectomy Model Rabbit

Abstract: Medium-chain triglycerides did not induce morphologic evidence of retinal toxicity. The results suggest that medium-chain triglycerides could be a promising alternative intraocular tamponading agent for the treatment of retinal detachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the form of an oil‐in‐water emulsion, MCTs have the potential to be used as drug carriers for sustained release of dexamethasone palmitate in vitreous cavity (Daull et al 2013). Furthermore, with physical properties similar to conventional SO, MCTs present great potential to be alternatives of SO as an intraocular tamponade agents in animal studies with no obvious retinal toxicity (Auriol et al 2013; Soler et al 2017).…”
Section: Novel Alternatives To So In Vitreoretinal Surgerymentioning
confidence: 99%
“…In the form of an oil‐in‐water emulsion, MCTs have the potential to be used as drug carriers for sustained release of dexamethasone palmitate in vitreous cavity (Daull et al 2013). Furthermore, with physical properties similar to conventional SO, MCTs present great potential to be alternatives of SO as an intraocular tamponade agents in animal studies with no obvious retinal toxicity (Auriol et al 2013; Soler et al 2017).…”
Section: Novel Alternatives To So In Vitreoretinal Surgerymentioning
confidence: 99%
“…Medium-chain triglycerides. Soler et al 81 and Auriol et al 82 reported the use of medium-chain triglycerides (MCTs) as a vitreous substitute.…”
Section: Pva-based Hydrogelmentioning
confidence: 99%
“…However, in vivo study showed that the MCT causes some emulsification and cataract formation in rabbit eyes. Auriol et al 82 performed in vivo study of the MCTs in minipigs and observed that in some of the cases, retinal detachment was not repaired even after 45 days. So, additional study must be needed for checking its potential as vitreous substitute.…”
Section: Pva-based Hydrogelmentioning
confidence: 99%